Membangun Karakter Unggul melalui Pelita Ilmu - Yasin, Muhamad (CV. Creative Tugu Pena, 2023)
The aim of this article is to provide a comprehensive analysis in order to improve the Islamic religious character education approach, so that it is more relevant, interesting and effective for the current generation. Writing this article uses a descriptive method to describe a phenomenon regarding character education issues through the Pelita Ilmu approach which is elaborated in the form of definitions originating from factual events in the Indonesian education system. Pelita Ilmu plays an important role in forming superior individual character. Pelita Ilmu functions as a source of religious knowledge, forms ethical awareness, strengthens character, and builds a strong Islamic identity. The Essence of Islam, Pelita Ilmu does not inform about the goals and practices of religion, but rather aims to shape good behavior, moral attitudes, and positive contributions to society. In the context of Islamic religious education, Pelita Ilmu plays an important role in forming superior individual character. As a source of in-depth religious knowledge, Pelita Ilmu not only presents religious teachings, but also guides individuals in applying Islamic values ??in everyday life. These integrated values ??are embedded in character education which not only benefits individuals personally but also contributes to a better society, a healthy work environment, and a positive influence on future development. Keywords : Islamic Religious Character, Education Character, Building Education Character